Comparing asexual and non-asexual sexual minority adolescents and young adults: stressors, suicidality and mental and behavioural health risk outcomes. Issue 2 (3rd April 2022) - McInroy, Lauren B.; Beaujolais, Brieanne; Leung, Vivian W. Y.; Craig, Shelley L.; Eaton, Andrew D.; Austin, Ashley
ABSTRACT: Despite increasing scholarship on sexual minority youth (SMY), little is known about the experiences and outcomes of those who identify as asexual. This study investigates how internal and external stressors, mental health and health risk behaviours differ between asexual youth and other SMY. The study uses a sub-group analysis ( n = 5, 314) of an online survey of self-identified sexual and gender minority youth (SGMY). Descriptive and inferential statistics compare asexual ( n = 669) to non-asexual ( n = 4, 645) respondents across two developmental phases – adolescence (age 14–19) and young adulthood (age 20–25) – while accounting for gender minority (e.g., transgender) self-identification. Results indicate that asexual youth had significantly higher internalised LGBTQ-phobia and tended to have poorer mental health (e.g., higher rates of depression), while having experienced less interpersonal discrimination/prejudice and having engaged in fewer health risk behaviours (e.g., substance use). Findings have implications for clinical practice. Future research should continue to investigate the impact of risk and protective factors on outcomes for asexual young people.